Environmental and ecological biochemistry - Hochachka, Peter W.; Mommsen, T. P. (Amsterdam ; New York : Elsevier, 1995)
This fifth volume in this established series deals with the biochemical responses of fish to different environmental/ecological factors. Topics covered include oxygen availability, effects of temperature and pressure, adverse effects of metabolites, effects of stress and many more. The book should be of interest to fish biochemists and physiologists, aquaculturists and many other fisheries and animal scientists.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Fishes -- Composition; Fishes -- Molecular aspects; Fishes -- Physiology; Electronic books